Anti-TNBC effects of Lappaol F by targeting epithelial-mesenchymal transition via regulation of GSK-3β/YAP/β-catenin and PI3K/AKT pathways - Meng, Qiqi; Li, Zhiping; He, Xiaofeng; Hu, Yuanhao; Wu, Guiyun; Huang, Jiawen; Luo, Zhuohui; Hu, Yingjie; Shen, Xiaoling (Frontiers in Pharmacology, 2025)
PurposeLappaol F (LAF), a lignan extracted from Fructus Arctii, has a wide spectrum of anti-tumor effects, including inhibition of TNBC cell growth. However, the pharmacological mechanism of LAF targeting epithelial-mesenchymal transition (EMT) to inhibit Triple-negative breast cancer (TNBC) growth remains poorly understood. The present study aimed to reveal the potential mechanism of LAF against TNBC by in vivo and in vitro experiments.MethodsIn situ, transplantation-induced MDA-MB-231 solid tumor model in NCG mice and cultured MDA-MB-231 and Hs-578T cells were used to evaluate the anti-TNBC effect of LAF. Flow cytometry, wound healing, transwell assay, western blot, RT-PCR, and immunofluorescence analysis were carried out to investigate the pharmacological mechanism of LAF against TNBC.ResultsLAF significantly inhibited the growth of MDA-MB-231 tumors, with downregulated tumor level of vimentin and upregulated level of ZO-1. In MDA-MB-231 and Hs-578T cells, LAF markedly suppressed cell proliferation, migration and invasion, and promoted apoptosis. Similarly, LAF increased the expression of ZO-1 and occludin proteins in MDA-MB-231 cells, and inhibited the expression of vimentin, snail and slug proteins in MDA-MB-231 and Hs-578T cells, as well as the expression of N-caderin in Hs-578T cells. Moreover, LAF also inhibited the phosphorylation of GSK-3β, thereby inhibited the downstream nuclear translocation of β-catenin and the expression of YAP. Furthermore, LAF significantly inhibited the expression of PI3K and AKT, and the phosphorylation of downstream mTOR.ConclusionLAF showed anti-TNBC effect both in vitro and in vivo. Reversal of EMT by inhibiting GSK-3β/YAP/β-catenin signaling and PI3K/AKT/mTOR signaling contributes to the effect.